Functional analysis of missense variants in the TRESK (KCNK18) K channel - Andres-Enguix, I; Shang, L; Stansfeld, P; Morahan, J; Sansom, M; Lafrenière, R; Roy, B; Griffiths, L; Rouleau, G; Ebers, G; Cader, Z; Tucker, S (Springer Nature, 2012)
A loss of function mutation in the TRESK K2P potassium channel (KCNK18), has recently been linked with typical familial migraine with aura. We now report the functional characterisation of additional TRESK channel missense variants identified in unrelated patients. Several variants either had no apparent functional effect, or they caused a reduction in channel activity. However, the C110R variant was found to cause a complete loss of TRESK function, yet is present in both sporadic migraine and control cohorts and no variation in KCNK18 copy number was found. Thus despite the previously identified association between loss of TRESK channel activity and migraine in a large multigenerational pedigree, this finding indicates that a single non-functional TRESK variant is not alone sufficient to cause typical migraine and highlights the genetic complexity of this disorder.